Betangas Ritual Penyucian Diri Perempuan Menjelang Pernikahan dalam Perspektif Budaya Palembang dan Kisah Ester - Lydia Kanti Rahayu (Sekolah Tinggi Agama Kristen Diaspora Wamena, 2026)
The betangas tradition is a ritual of self-purification for women in Palembang, performed in the run-up to their wedding. This ritual serves not only as a form of physical care, but also carries symbolic meaning representing a woman’s physical and spiritual readiness to embark on a new chapter as a wife. This study aims to uncover the symbolic meanings contained within the betangas tradition and to explore the parallels between its values and the process of self-purification undergone by Queen Esther as described in the Bible. The research methods employed include descriptive qualitative analysis, direct observation, in-depth interviews, and a review of various written sources, including books, academic articles, and biblical commentaries. The research findings indicate that every stage of the betangas ritual—from the body scrub, the use of spices, to the steam bath—contains symbols of self-purification, renewal, and spiritual readiness. The aroma of the spiced steam is believed to have a dual meaning: in addition to cleansing the body, it also symbolises prayer and hope for a peaceful and harmonious married life. The connection with the story of Queen Esther is evident in the values of purity, sincerity of heart and inner readiness, which underpin both rituals. Esther’s twelve-month period of self-purification using myrrh oil and aromatic herbs holds a parallel meaning to betangas, namely a process of self-transformation that prepares women to embrace new roles and life’s responsibilities. Abstrak Tradisi betangas merupakan ritual penyucian diri bagi perempuan Palembang yang dilaksanakan menjelang pernikahan. Ritual ini tidak hanya berfungsi sebagai perawatan tubuh, tetapi juga mengandung makna simbolik yang merepresentasikan kesiapan lahir dan batin seorang perempuan dalam memasuki babak baru sebagai seorang istri. Penelitian ini bertujuan untuk mengungkap makna simbolik yang terkandung dalam tradisi betangas serta menelusuri persinggungan nilai-nilainya dengan proses penyucian diri yang dijalani Ratu Ester sebagaimana yang dalam Alkitab. Metode penelitian kualitatif deskriptif dan pengamatan langsung, wawancara mendalam, serta telaah terhadap berbagai sumber tertulis termasuk buku, artikel ilmiah, dan penafsiran Alkitab. Hasil penelitian menunjukkan bahwa setiap tahap dalam betangas yang dimulai dari luluran, penggunaan rempah-rempah, hingga proses mandi uap. Semua proses tersebut mengandung simbol penyucian diri, pembaharuan, dan kesiapan spiritual. Aroma uap rempah diyakini memiliki makna ganda: selain membersihkan tubuh, ia juga melambangkan doa dan harapan bagi cita-cita akan kehidupan rumah tangga yang tenteram dan harmonis. Keterkaitan dengan kisah Ratu Ester tampak pada nilai-nilai kemurnian, kertulusan hati, dan kesiapan batin yang sama-sama mendasari kedua ritual tersebut. Periode penyucian diri Ester selama dua belas bulan dengan minyak mur dan ramuan aromatik memiliki kesepadanan makna dengan betangas, yaitu proses perubahan diri yang mempersiapkan perempuan untuk menerima peran dan amanat hidup yang baru.